The Effect of Pineapple Juice on Menstrual Pain Intensity among Adolescents - Astri Ulina Saragih; Novita Br Ginting Munthe; Risky Yulanda; Santa Natalia (JURNAL KEBIDANAN KESTRA (JKK), 2026)
Dysmenorrhea is a common problem among adolescent girls and can interfere with daily activities. One non-pharmacological therapy is pineapple juice, which contains bromelain enzyme as a natural anti-inflammatory agent. This study aimed to determine the effect of pineapple juice on menstrual pain intensity among adolescents at SMA Nusantara Lubuk Pakam. This study used a quasi-experimental design with a pretest-posttest without control group approach. The sample consisted of 30 adolescent girls experiencing menstrual pain selected using purposive sampling. Pain intensity was measured using the Numeric Rating Scale (NRS) before and after intervention. The intervention was the administration of 250 ml pineapple juice for 3 days during menstruation. The results showed that the mean pain intensity before intervention was 6.2 (SD=1.1) and decreased to 3.1 (SD=1.0) after intervention. The Wilcoxon test showed a p-value of 0.000 (p<0.05), indicating a significant effect of pineapple juice on reducing menstrual pain intensity. In conclusion, pineapple juice is effective as a non-pharmacological therapy to reduce menstrual pain in adolescents.